Identifikasi Tipe Dehidrasi dan Profil Elektrolit Mayor pada Pasien Kucing di Rumah Sakit Hewan Prof. Soeparwi dan Beberapa Klinik Hewan di Wilayah Yogyakarta - Guntari Titik Mulyani; Setyo Budhi; Kurnia . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
Dehydration is defined as a lack of body fluids followed by loss of electrolytes, and changes in acid-base balance. The type of dehydration is limited based on the concentration of sodium in serum at the time of dehydration. Maintenance of osmotic pressure and distribution of several compartments of body fluids are the main functions of the four major electrolytes, namely sodium (Na +), potassium (K +), chloride (Cl‾), and bicarbonate (HCO3‾). Sodium is the most cation in extracellular fluid, most potassium cation in intracellular fluid and chloride is the most anion in extracellular fluid. The purpose of this study was to identify the type of dehydration and to determine the major electrolyte profile in cats in Yogyakarta and its surroundings. This study used 18 sick cats that were thought to be dehydrated, marked by decreased skin turgor, CRT> 2 seconds, and 12 cats that were suspected of having electrolyte balance disorders with symptoms of ascites, uropoetic disorders. Blood was drawn for all cats to measure Pack Cells Volume (PCV) levels. Patient clinical data and patient diagnosis were recorded, cats with changes in serum PCV levels were separated for examination of levels of sodium, chloride, potassium using Seamaty SMT-120V. The type of dehydration is identified based on the sodium level in the serum of a dehydrated cat. The results showed that most of the cat patients were dehydrated had low serum sodium levels (hyponatremia). There was 1 cat patient had low chloride levels. Potassium levels in cats with UT obstruction increased, which led to a decrease in the Na: K ratio. Cat bicarbonate levels did not show any change. From the results of the study it was concluded that dehydration in cats at Prof. Soeparwi is hypotonic dehydration (71%). The sodium profile mostly decreased, chloride and bicarbonate levels did not change, while there were changes in potassium levels in patients with UT disorders. The advice given is to check electrolytes before doing fluid therapy. Prior to electrolyte testing, dehydrated cats can be given a sodium solution.